Juridical analysis of land rights release with ownership certificates purchased by limited liability companies from land law perspective - Christian Jericho; Laily Washliati; Erniyanti Erniyanti (Annals of Justice and Humanity, 2025)
Purpose: This study aims to analyze the legal framework for the release of Freehold Title (SHM) land purchased by Limited Liability Companies (PT) in Batam. It focuses on the regulatory basis, implementation practices, and the challenges and solutions in the conversion process to Right to Build (HGB). Methodology: The research employs a descriptive sociological-juridical method combined with a normative legal approach to examine secondary data, and an empirical approach to gather primary data through field research. The analysis integrates statutory interpretation and practical observations from stakeholders. Results: Findings reveal that SHM land purchased by a PT must first be released and transferred to the state before being converted to HGB. The process involves drafting a deed of release before a notary, fulfilling BP Batam’s regulatory requirements, and submitting an HGB application to BPN under Minister of ATR/BPN Regulation No. 5 of 2025. Conclusion: The legal certainty of land release in Batam depends on technical regulations, institutional coordination, and digital integration. While the current system provides a mechanism, procedural and administrative delays persist. Limitations:The study is limited to the Batam context and relies on selected field data. Broader generalization may require comparative studies across other special economic zones in Indonesia. Contribution: This research contributes to the discourse on land law reform in Indonesia by offering practical legal solutions, including the need for technical regulations on release deeds, improved inter-agency coordination, and digital land information systems to ensure efficiency and certainty in land rights conversion.